Xylanase and stimbiotic supplementation improve broilers performance and nutrient digestibility across both wheat-barley and corn-based diets - Mehdi Toghyani; Eunjoo Kim; Shemil P. Macelline; Gemma González-Ortiz; Reza Barekatain; Sonia Y. Liu (Poultry Science)
The present study investigated the effects of supplemental xylanase or stimbiotic in male broiler chickens fed either corn- or wheat-barley-based diets. A total of 1,296 Ross 308 day-old chicks were assigned to a 2 × 3 factorial design, evaluating the effects of diet grain source (wheat-barley or corn) and additives (none, xylanase, or stimbiotic). The stimbiotic used in the present study contained xylanase and fermentable xylo-oligosaccharides. Each treatment was replicated 8 times, with 27 birds per replicate pen. At day 21, 3 birds per pen were selected for blood sample collection and another 3 birds at day 27 for digesta collection. The final body weight at day 42 was not statistically affected by grain source, additive supplementation, or their interaction (P > 0.05). Over the entire production period (0–42 d), an interaction between grain source and additive supplementation was found for feed conversion ratio (FCR), where xylanase or stimbiotic improved the FCR across the diet type, with a more pronounced improvement achieved when supplemented to the wheat-barley based diets (P < 0.01). A feed grain × additive interaction resulted in lower total feed intake in birds fed the wheat-barley based diets only in response to stimbiotic (P < 0.05). Ileal viscosity was also affected by an interaction between grain source and additive supplementation, in which viscosity reduction by xylanase or stimbiotic was only achieved in birds fed the wheat-barley based diets (P < 0.01). Similarly, an interaction was found in the ileal digestibility coefficient of protein (P = 0.016) and starch (P = 0.006), where either xylanase or stimbiotic improved the digestibility only in birds offered the wheat-barley based diets. Serum fluorescein isothiocyanate dextran level was higher in birds fed the corn-based diets compared to those fed the wheat-barley based diets (P < 0.01). These results suggest that dietary supplementation with either xylanase or stimbiotic improved feed efficiency, regardless of the dietary grain source, likely through enhanced nutrient digestibility and/or reduced digesta viscosity.